RETRACTED: Modeling patterns of human well-being in the context of sustainable development and digital transformation - Makhosheva Salima; Kandrokova Marina; Shakhgiraev Ismail (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001